2005
DOI: 10.1097/01.mcp.0000147861.60768.24
|View full text |Cite
|
Sign up to set email alerts
|

Asthma epidemiology: has the crisis passed?

Abstract: Because reasons for the original increases in asthma prevalence remain unclear, an explanation for the apparent stabilization of asthma prevalence reported in some studies also remains elusive. This is compounded by the difficulty in defining asthma accurately in population studies and inconsistencies in the results of prevalence estimation among repeated cross-sectional studies. Efforts should be made to continue monitoring asthma prevalence and to begin monitoring asthma prevalence in regions where environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…These results are in keeping with other reports of diagnostic exchange (Burney et al 1990;Dodge et al 1986;Fletcher 1978;Lundback et al 2001;Tinkelman et al 2006). Our finding of stabilized rates of asthma prevalence in more recent years has also been observed by others (Lawson and Senthilselvan 2005).…”
Section: Figure 2 Prevalence Of Respiratory Diseases Over Time Agessupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in keeping with other reports of diagnostic exchange (Burney et al 1990;Dodge et al 1986;Fletcher 1978;Lundback et al 2001;Tinkelman et al 2006). Our finding of stabilized rates of asthma prevalence in more recent years has also been observed by others (Lawson and Senthilselvan 2005).…”
Section: Figure 2 Prevalence Of Respiratory Diseases Over Time Agessupporting
confidence: 83%
“…n Manitoba, as in Canada and elsewhere, many studies have reported increasing rates of asthma prevalence over time, especially among children (Akinbami and Schoendorf 2002;Burney et al 1990;Erzen et al 1995;Garner and Kohen 2008;Kozyrskyj and Hildes-Ripstein 2002;Kozyrskyj et al 2004;Lawson and Senthilselvan 2005;Lundback et al 2001;Manfreda et al 1993;Mannino et al 2002;Millar and Hill 1998;Moorman et al 2007;Senthilselvan et al 2003;Senthilselvan 1998). This "asthma epidemic" has raised concern among clinicians, researchers, policy makers and the public, sparking new studies to understand the causes of this increase.…”
mentioning
confidence: 99%
“…While recent data suggest that the trend of prevalence, at least for asthma, may be reaching a plateau, the number of patients with other allergic disorders such as rhinitis, urticaria and food and drug allergy is expected to continue to rise [1]. Anaphylaxis is the most dramatic clinical presentation of allergy and is frequently a medical emergency in both paediatric and adult patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from around the world suggest that the incidence and prevalence of asthma began to increase more than two decades ago, with no sign that these disturbing trends may be reversing [1]. Asthma is characterized by episodic dyspnea, airway obstruction, mucus cell metaplasia and T-helper cell type 2 (Th2)-dependent inflammation of the lung.…”
mentioning
confidence: 99%